Antioxidant and toxicity properties of anthocyanin extracted from red flower of four tropical shrubs - HARLINDA KUSPRADINI; ANINDYA MARSABELLA ROSIARTO; AGMI SINTA PUTRI; IRAWAN WIJAYA KUSUMA (Smujo International, 2016)
Abstract. Kuspradini H, Rosiarto AM, Putri AS, Kusuma IW. 2016. Antioxidant and toxicity properties of anthocyanin extracted from red flower of four tropical shrubs. Nusantara Bioscience 8: 135-140. Some of flowers are colored by anthocyanins and make their own shade profile. Anthocyanins are natural colorants which have gained a growing interest due to their extensive range of colors and beneficial health effects. Anthocyanin content, antioxidant and toxicity activity of four red flowers (Bougainvillea glabra, Jatropha integerrima, Melastoma malabathricum, and Mussaenda philippica) has been evaluated in this study by pH-differential, DPPH and Brine Shrimp Lethality method, respectively. In this present work, 1% HCl-ethanol and ethanol solvent were used for the extraction. The extractive yield was varied in different extraction system, 5.80 to 13.30% in 1% HCl-ethanol and 6.29 to 8.81% in ethanol solvent. The IC50 of antioxidant from different extraction systems were also varied, whereas the acidified ethanol extracts showed the highest scavenging activity than the ethanol extracts, 11.67 to 46.38 ppm and 79.08 to 133.35 ppm, respectively. The free radical scavenging action of 1% HCl-ethanol extracts of flower is in the order as J. integerrima > M. malabathricum > M. philippica > B. glabra while in the ethanol extracts are in the order as M. malabathricum > J. integerrima > B. glabra >M. philippica. In the group of 1% HCl-ethanol extracts, Jatropha integerrima Jacq was the richest in anthocyanin content (15.83 mg CGE/100 g DW) and showed the strongest antioxidant activity (11.67 ppm) and not toxic. Therefore, these can be regarded as a potential pigment source for food and natural product applications.